Assessing moisture sources of precipitation in the Western Pamir Mountains (Tajikistan, Central Asia) using deuterium excess. Issue 1 (1st January 2019) - Juhlke, Tobias R.; Meier, Christiane; van Geldern, Robert; Vanselow, Kim A.; Wernicke, Jakob; Baidulloeva, Jamila; Barth, Johannes A.C.; Weise, Stephan M.
Abstract: Air moisture of oceanic origin can be subject to long-range transport and could contribute to precipitation at distant places. With ongoing climate change the relationship between water vapour sources and sinks is under constant evolution and plays an important role for water budget assessments. This study analysed monthly integrated and event-based precipitation samples from two field sites in the Western Pamir Mountains (Tajikistan) for stable isotope compositions of oxygen ( δ 18 O) and hydrogen ( δ 2 H) of water. The aim was to investigate water vapour sources and, in particular, to evaluate contributions of water vapour from the Mediterranean region. The latter has been often postulated as a potential moisture source region for Central Asia. Deuterium excess values ( d ), that serve as a fingerprint of moisture origin, were below 13‰ in monthly integrated samples, for most of the year. This indicates a smaller contribution of high Mediterranean moisture (∼20‰) to the Western Pamir Mountains than originally expected. A maximum d value of 19‰ was observed in March, which is not in agreement with the common observation of increased Mediterranean contribution during winter (DJF). A Lagrangian backward trajectory model (HYSPLIT) was applied to infer the general air mass origin for sampled precipitation events. A maximum contribution of 'western' moisture of 40% was also detected in March, while 40%–60% of moisture that contributed to precipitation events in winter was transported by trajectories that originated from the Northern Indian Ocean.